2005
DOI: 10.1038/modpathol.3800336
|View full text |Cite
|
Sign up to set email alerts
|

Increased endostatin/collagen XVIII expression correlates with elevated VEGF level and poor prognosis in hepatocellular carcinoma

Abstract: Liver is the primary source for collagen XVIII, the precursor of angiogenesis inhibitor, endostatin. However, the role of endostatin/collagen XVIII expression during liver carcinogenesis remains elusive. Therefore, we studied its expression in five hepatoma cell lines and 105 hepatocellular carcinoma specimens. The poorly differentiated hepatoma cell lines exhibited increased endostatin/collagen XVIII levels compared with the well-differentiated ones. In hepatoma tissues, endostatin/collagen XVIII expression w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0
4

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(28 citation statements)
references
References 27 publications
(37 reference statements)
3
21
0
4
Order By: Relevance
“…Состав и структура ГСПГ подвергаются значитель-ным изменениям в опухолях яичников и молочной железы человека [46,47]; экспрессия синдекана 1, де-корина и люмикана значительно изменяется в опухолях молочной железы [48], глипиканы вовлечены в процесс канцерогенеза в тканях легкого [49] и поджелудочной железы [50]; синдеканы участвуют в патогенезе лимфомы Ходжкина [51]; экспрессия перлекана и серглицина значительно снижается в клетках лимфомы Беркитта [52]; уровень экспрессии коллагена 18 ассоциируется с прогрессированием и прогнозом гепатоцеллюлярной карциномы [53], а в опухолях прямой кишки проис-ходит одновременное снижение уровней экспрессии декорина и перлекана (в 2 раза) и повышение экспрес-сии бигликана и версикана (в 6 и 3 раза соответственно) [54]. ПГ глипиканы, агрин, версикан и декорин при-нимают активное участие в развитии злокачественных [55].…”
Section: функциональная роль протеогликанов при канцерогенезеunclassified
“…Состав и структура ГСПГ подвергаются значитель-ным изменениям в опухолях яичников и молочной железы человека [46,47]; экспрессия синдекана 1, де-корина и люмикана значительно изменяется в опухолях молочной железы [48], глипиканы вовлечены в процесс канцерогенеза в тканях легкого [49] и поджелудочной железы [50]; синдеканы участвуют в патогенезе лимфомы Ходжкина [51]; экспрессия перлекана и серглицина значительно снижается в клетках лимфомы Беркитта [52]; уровень экспрессии коллагена 18 ассоциируется с прогрессированием и прогнозом гепатоцеллюлярной карциномы [53], а в опухолях прямой кишки проис-ходит одновременное снижение уровней экспрессии декорина и перлекана (в 2 раза) и повышение экспрес-сии бигликана и версикана (в 6 и 3 раза соответственно) [54]. ПГ глипиканы, агрин, версикан и декорин при-нимают активное участие в развитии злокачественных [55].…”
Section: функциональная роль протеогликанов при канцерогенезеunclassified
“…Phase II clinical trials using recombinant endostatin for treatment of advanced neuroendocrine tumors showed 80% of stable disease, although no patient displayed partial or complete response, according to the WHO criteria [9]. Elevated serum levels of endostatin are associated with poor outcome in several cancers [10][11][12][13][14][15][16][17][18]. Endogenous serum level of endostatin may reflect counteractions with active angiogenesis in tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Controversy exists, on the other hand, as to whether collagen XVIII levels in tumor hepatocytes increase or decrease with HCC progression. While some authors demonstrate that high tumoral expression of collagen XVIII correlates with increased VEGF activity and poor prognosis (Hu et al, 2005), others argue that, as it can be expected of an angiogenesis suppressor, collagen XVIII becomes downregulated by HCC cells in parallel with increasing tumor size, microvessel density, and clinical aggressiveness (Musso et al, 2001b). Since long collagen XVIII variants are regulated by liver-specific transcription factors, it has been suggested that their downregulation may reflect the loss of hepatocytic phenotype.…”
Section: Modular Hspgs Of the Basement Membrane: Perlecan Agrin Andmentioning
confidence: 99%